Investigation of Electrochemical Behaviour of Quercetin on the Modified Electrode Surfaces with Procaine and Aminophenyl in Non-Aquous Medium - Ibrahim Ender Mulazimoglu; Erdal Ozkan (E-Journal of Chemistry)
In this study, cyclic voltammetry and electrochemical ımpedance spectroscopy have been used to investigate the electrochemical behaviour of quercetin (3,3′,4′,5,7-pentahydroxyflavone) on the procaine and aminophenyl modified electrode. The modification of procaine and aminophenyl binded electrode surface with quercetin was performed in +0,3/+2,8 V (for procaine) and +0,4/+1,5 V (for aminophenyl) potential range using 100 mV s-1 scanning rate having 10 cycle. A solution of 0.1 M tetrabutylammonium tetrafluoroborate in acetonitrile was used as a non-aquous solvent. For the modification process a solution of 1 mM quercetin in 0.1 M tetrabutylammonium tetrafluoroborate was used. In order to obtain these two surface, a solution of 1 mM procaine and 1 mM nitrophenyl diazonium salt in 0.1 M tetrabutylammonium tetrafluoroborate was used. By using these solutions bare glassy carbon electrode surface was modified. Nitrophenyl was reduced to amine group in 0.1 M HCl medium on the nitrophenyl modified glassy carbon elelctrode surface. Procaine modified glassy carbon electrode surface was quite electroactive. Although nitrophenyl modified glassy carbon elelctrode surface was electroinactive, it was activated by reducing nitro group into amine group. For the characterization of the modified surface 1 mM ferrocene in 0.1 M tetrabutylammonium tetrafluoroborate for cyclic voltammetry and 1 mM ferricyanide/ferrocyanide (1:1) mixture in 0,1 M KCl for electrochemical impedance spectroscopy were used.